Marketing communications in health and medicine: perspectives from Willis-Knighton Health System - James K. Elrod; John L. Fortenberry (BMC, 2020)
Abstract Background Communications prowess is a key ingredient of productive healthcare delivery pursuits, with associated successes clearly positioning health and medical establishments for growth and prosperity. Many conveyance mechanisms are at the disposal of healthcare providers, permitting numerous opportunities for engaging current and prospective patients. For the best communicative outcomes, all must be considered when formulating marketing communications initiatives, with consideration first, of course, requiring that healthcare providers acquire an understanding of communications options and associated fundamentals. Discussion In pursuing knowledge of communications options and related guidance, healthcare providers can benefit greatly by gaining operational perspectives from peer institutions. Over many decades, through scores of deployments, Willis-Knighton Health System has acquired significant communications prowess, prompting development of this special supplement in BMC Health Services Research, entitled "Marketing communications in health and medicine: perspectives from Willis-Knighton Health System," with this particular article supplying a brief profile of the contents included in the associated supplement. Across the pages of the collection of articles contained in the supplement, attention specifically is directed toward the components of the marketing communications mix, foundational elements of communication, the patronage process, and the necessity for integrating marketing communications. Conclusions Establishing an effective dialogue with current and prospective patients is an absolute necessity for healthcare organizations, warranting intensive efforts to master marketing communications. Given the imperative for excellence in marketing communications, it is hoped that the light shed by this supplement and its collection of articles will help healthcare providers better understand marketing communications and deploy associated initiatives successfully, affording greater patient engagement opportunities.